Arrhythmia in patients with systemic sclerosis: incidence, risk factors and impact on mortality in a Swedish register-based study - Pontus Andell; Marie Holmqvist; Roger Hesselstrand; Majd Bairkdar; Zihan Dong (RMD Open)
Objectives The objectives of this study are to study the risk of developing cardiac arrhythmia and its subtypes over time in patients with systemic sclerosis (SSc), to assess potential risk factors for arrhythmia in SSc and to explore whether arrhythmia is associated with mortality.Methods We used nationwide Swedish registers to identify patients with incident SSc 2004–2019 and matched general population comparators (1:10). The primary outcome was incident arrhythmia. Follow-up started at the date of SSc diagnosis and ended at the primary outcome, death, emigration or 31 December 2019. We estimated the incidence of arrhythmia overall and stratified by subtype and explored the relative risk in relation to time since diagnosis using flexible parametric models. We used Cox regression to study risk factors for arrhythmia and the association of arrhythmia with mortality.Results We identified 1565 patients and 16 009 comparators. The overall incidence of arrhythmia was 255 (95% CI 221 to 295) and 119 (95% CI 112 to 127) per 10 000 person years in patients with SSc and comparators, respectively, corresponding to an IRR of 2.1 (95% CI 1.8 to 2.5). The greatest hazard difference between patients with SSc compared with the comparators was seen in the first year of follow-up (HR for arrhythmia 3.0; 95% CI 2.3 to 3.8). Atrial fibrillation and flutter were the most common arrhythmia subtypes. Male sex, index age and pulmonary arterial hypertension were significant risk factors for arrhythmia in SSc. Incident arrhythmia was significantly associated with mortality (HR 2.2; 95% CI 1.6 to 3.0).Conclusion SSc is associated with higher incidence of cardiac arrhythmia compared with general population. Arrhythmia seems to be an early manifestation of SSc and is associated with higher mortality.